Mapping HOTS in Textbook Assessment Items: Implications for Instructional and Learning Quality - Yeni Witdianti; Nursalim; Juwilsi Thianci Rawung; Martina L Suarlembit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The main problem in Indonesian language learning at the high school level is the low application of Higher Order Thinking Skills (HOTS) aspects in evaluation questions, which impacts the development of students' critical, analytical, and creative thinking abilities. This study is motivated by the need to improve the quality of learning thru assessments that demand higher-order thinking skills. This study aims to analyze and evaluate the representation of HOTS aspects in the evaluation questions within the Tiga Serangkai Indonesian Language textbook for SMA Class X, and to assess its implications for the quality of learning. The research subject is the evaluation questions in the Indonesian textbook